Thorium Ion Uptake by Zeolite a Synthesized from Natural Clinoptilolite Tuffs - H. Faghihian; M.G. Maragheh; M.K. Amini; A.R. Nezamzadeh (Adsorption Science & Technology)
Natural clinoptilolite tuffs from the Semnan region of Iran were used for the synthesis of zeolite A. The tuffs and synthesized zeolite were characterized by XRD and XRF methods. The sorption behaviour of the synthesized zeolite towards thorium ions was studied. The corresponding adsorption constant was calculated using the Lagergren equation. The measured values of the distribution coefficient (K d ) indicated that Th(IV) ion uptake was higher at lower initial concentrations, higher temperature and higher pH values. The thermodynamic parameters for the exchange were calculated through the construction of ion-exchange isotherms at 298, 323 and 343 K, respectively. The dynamic adsorption of Th(IV) ions was also studied by passing the solution through a column in the presence and absence of sodium ions.